2019
DOI: 10.4314/ijbcs.v13i2.21
|View full text |Cite
|
Sign up to set email alerts
|

La toxicité subaiguë de l’écorce de racines de <i>Dichrostachys cinerea</i> (L.) Wight et Arn. (Fabaceae)

Abstract: RESUME L'écorce de racines de Dichrostachys cinerea (L.) Wight et Arn. (Fabaceae) est traditionnellement utilisée, par trituration aqueuse en instillations nasales, pour traiter l'asthme en Côte d'Ivoire. Des propriétés antispasmodiques sur la musculature lisse du tractus respiratoire d'une part, des propriétés antioxydante et analgésique d'autre part, d'un extrait hydro-éthanolique de cette partie de la plante, ont précédemment été mises en évidence. Les présentes investigations ont consisté en l'évaluation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The results obtained on the various parameters (urea, creatinine, GGT, ALT, AST and ALP) by ASARE et al [17] who worked on the acute toxicity of Phyllanthus niruri aqueous extract on female Sprague-Dawley (S-D) rats showed that there was no significant difference either for the dose of aqueous extracts at 2000 mg/kg body weight than at 5000 mg/kg body weight. Our results on the same biochemical parameters (Tables 4, 6 and 7) corroborate those of Asare et al [12] in Wistar albino rats poisoned by lead acetate and treated with P. odontadenius extracts at doses of 250 and 500 mg/kg body weight. On the other hand, in NMRI albino mice subjected to a single dose of 2000 mg/kg of body weight, significant differences were found for three biochemical parameters including urea, ALT and GGT.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results obtained on the various parameters (urea, creatinine, GGT, ALT, AST and ALP) by ASARE et al [17] who worked on the acute toxicity of Phyllanthus niruri aqueous extract on female Sprague-Dawley (S-D) rats showed that there was no significant difference either for the dose of aqueous extracts at 2000 mg/kg body weight than at 5000 mg/kg body weight. Our results on the same biochemical parameters (Tables 4, 6 and 7) corroborate those of Asare et al [12] in Wistar albino rats poisoned by lead acetate and treated with P. odontadenius extracts at doses of 250 and 500 mg/kg body weight. On the other hand, in NMRI albino mice subjected to a single dose of 2000 mg/kg of body weight, significant differences were found for three biochemical parameters including urea, ALT and GGT.…”
Section: Discussionsupporting
confidence: 91%
“…The toxic effects of a substance are the result of biochemical interactions between the substance and/or its metabolites and the structures of the organism to which it is administered, probably justifying the almost constant evaluation of biochemical and hematological parameters during toxicological studies [12]. This is where this study is justified in order to understand the acute toxicity and in vivo antioxidant activity of P. odontadenius, which until now seems to have never been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This same method was used by [17] who showed that the LD50 of ETAAC is greater than 5000 mg/kg of bw. Evaluating the signs of clinical and / or biological intoxication linked to repeated use of medicinal plants is judicious, especially since the acute use of medicinal plants is rather rare in traditional medicine [18] . Thus after daily administration of ETAAC at doses of 100 mg/kg of bw, 200 mg/kg of bw and 400 mg/kg of bw for 28 days and 60 days, the comparison of the values was made between the treated rats and the controls.…”
Section: Discussionmentioning
confidence: 99%